223k views
5 votes
Help meee pleaseeee pleasee

Help meee pleaseeee pleasee-example-1

1 Answer

7 votes

Answer:

f(x) = (-1/4)x - 5

Explanation:

(-8, -3), (-12, -2)

(x₁, y₁) (x₂, y₂)

y₂ - y₁ -2 - (-3) -2 + 3 1 -1

m = ------------ = ------------- = ----------- = --------- = -------

x₂ - x₁ -12 - (-8) -12 + 8 -4 4

y - y₁ = m(x - x₁)

y - (-3) = (-1/4)(x - (-8)

y + 3 = (-1/4)(x + 8)

y + 3 = (-1/4)x - 2

-3 -3

-------------------------------

y = (-1/4)x - 5

I hope this helps!

User Marzieh Mousavi
by
5.0k points